A case report of hereditary neuropathy with liability to pressure palsies accompanied by type 2 diabetes mellitus and psoriasis. Issue 19 (May 2017) - Li, Jing; Niu, Bing; Wang, Xiaoling; Hu, Huaiqiang; Cao, Bingzhen
Abstract: Rationale: Hereditary neuropathy with liability to pressure palsy (HNPP) is an episodic, multifocal neuropathy, with a typical clinical presentation of recurrent transient pressure palsies, which is induced by a PMP22 deletion. Another neuropathy caused by a PMP22 duplication is Charcot-Marie-Tooth disease type 1A (CMT1A). PMP22 is a gene coding a protein called peripheral myelin protein 22 (PMP22), which plays an essential role in the formation and maintenance of compact myelin. Coexistence of type 2 diabetes mellitus (T2DM) and CMT1A has been reported in many work, however HNPP patients with T2DM are rare, and comorbidity of HNPP and psoriasis has not been reported previously. Electrophysiological features of HNPP has been found progressing with aging. Patient concerns: Here we present a 20-year-old man who exhibited lower extremity weakness and foot drop as the initial manifestation. Diagnoses: HNPP was diagnosed on the basis of clinical features, positive sural nerve biopsy findings, and genetic testing results. Moreover, physical examination, blood/urine glucose test, and diabetes-related autoantibodies investigations demonstrated that he had psoriasis and T2DM. The electrophysiological manifestations revealed profound demyelinating injuries and axonal injuries in distal peripheral nerves and facial nerves, which were more severe than general HNPP cases. Interventions: The young patient was treated with continuous subcutaneous insulin infusion and blood glucose monitoring, and then transferred to oral acarbose therapy. The psoriatic lesions were treated with calcipotriol ointment. Outcomes: In the follow-up, the right leg weakness was alleviated, and his gait was improved. Lessons: The findings indicate that diabetes mellitus may have an impact on the severity of HNPP. Physicians should consider that worsening of symptoms might result from newly diagnosed diabetes mellitus while treating patients with HNPP. Abstract : Supplemental Digital Content is available in the text